The Role of Knowledge and Attitude as Determinants of Adolescent Girls’ Compliance with Iron Tablet Consumption - Ahmad Dwiky Darmawan; Sulastri Sulastri (GLOBAL HEALTH SCIENCE GROUP, 2026)
Anemia remains one of the most significant global nutritional problems, particularly affecting adolescent girls. In Indonesia, the government has implemented a preventive strategy through the Weekly Iron and Folic Acid Supplementation (WIFAS) program, commonly known as tablet tambah darah (TTD). However, the success of this program relies heavily on adolescents’ adherence to regular consumption. Knowledge and attitude are recognized as key psychological determinants influencing compliance with iron supplementation. This study aimed to examine the correlation between knowledge and attitude with compliance in iron tablet consumption among adolescent girls at SMA Negeri 2 Sukoharjo. A descriptive correlational design with a quantitative approach was employed, involving 100 female students from grade XI selected using purposive sampling. Data were collected through a structured questionnaire measuring knowledge, attitude, and compliance variables. The instrument demonstrated good validity with Pearson Product Moment correlation coefficients ranging from 0.54 to 0.88 and acceptable reliability with a Cronbach’s Alpha value of 0.79. Statistical analysis was performed using the Chi-Square test at a significance level of p < 0.05. The majority of respondents had good knowledge (59%), positive attitudes (73%), and high compliance (44%) toward TTD consumption. The Chi-Square test showed a significant association between knowledge and compliance (p = 0.010), as well as between attitude and compliance (p = 0.010). The study concludes that knowledge acts as a primary cognitive factor influencing adolescents’ compliance with iron tablet intake, while attitude serves as a reinforcing element that strengthens behavioral intention and consistency.